Pengaruh model pembelajaran cooperative integrated reading and composition (circ) terhadap keterampilan menulis teks iklan peserta didik kelas v sd se-gugus anggrek kecamatan sukoharjo - Nur Ika Anna Fadhilah; Supianto Supianto (Universitas Sebelas Maret, 2025)
Abstract. This study aims to determine the effect of Cooperative Integrated Reading and Composition (CIRC) learning model on students skills in writing advertising texts. This study was conducted using a quasi-experimental method with a pretest-posttest control group design involving fifth grade students of Gugus Anggrek Elementary School, Sukoharjo Regency. The experimental group was taught using the CIRC model, while the control group used the Project Based Learning (PjBL) model. Data collection was carried out through a writing test, and the results were analysed using an independent sample t-test. The results showed that the average posttest score of the experimental group was significantly higher than the control group, with a significance value of 0,027 (r<0,05). The results showed that the CIRC model had a positive and significant effect on students advertising text writing skills. CIRC effectively engages students in collaborative reading and writing activities, encourages active participation, critical thinking, and structured composition. This model is recommended as an innovative learning approach to improve students writing performance, especially in persuasive text genres such as advertising. Keyword: cooperative integrated reading and composition, project based learning, writing skills, advertising text, elementary school